Responsiveness and clinical utility of PROMIS instruments in pediatric Crohn's disease: insights from a longitudinal study - Azevedo, Sara; Oliveira, Maria Miguel; Nogueira, Paulo; Lopes, Ana Isabel (Frontiers in Pediatrics, 2025)
BackgroundInflammatory bowel disease (IBD) may adversely affect physical, psychological, and social well-being. Integrating patient-reported outcomes (PROs) into clinical practice is crucial for comprehensive disease management.ObjectiveTo evaluate the responsiveness and clinical utility of Patient-Reported Outcomes Measurement Information System (PROMIS) instruments, compared with standard clinical assessment tools in pediatric CD patients.MethodsA longitudinal, prospective study with 31 pediatric Crohn's disease (CD) patients aged 8–17 years recruited from a Pediatric Gastroenterology Unit. Data were collected at baseline and every 6 months over 18 months. PROMIS pediatric measures assessed PROs. Disease activity was evaluated using the pediatric Crohn's disease activity index (PCDAI) and clinical markers. IMPACT-III was also applied. Linear mixed-effects models (LMMs) and bivariate analyses were used to assess changes over time.ResultsPROMIS Global Health scores showed significant improvement over time, indicating enhanced overall health perceptions among patients. Notable reductions were observed in PROMIS Pain Interference and Fatigue scores, indicating better physical health. PROMIS depression scores generally decreased, suggesting improved mental health. PCDAI scores, hemoglobin, and platelet count significantly changed and correlated with PROMIS measures. Globally, the study demonstrated significant and clinically relevant changes in multiple PROMIS measures, confirming their responsiveness to changes in disease activity.ConclusionPROMIS instruments are clinically useful in managing pediatric CD, providing valuable insights into global health and quality of life. Integrating PROMIS measures into routine clinical practice may enhance disease management and treatment strategies for pediatric IBD patients.